Professional Experience in Investigative Interviewing Does Not Guarantee Strong Knowledge about Memory - Dodier, Olivier; Tomas, Frédéric; Payoux, Mélany; Elissalde, Benjamin (Psychological Research on Urban Society, 2019)
We examined the knowledge of law enforcement officers regarding memory by conducting two levels of analysis. First, we compared memory-related knowledge and erroneous beliefs of officers (n = 200) and lay people (n = 403) and found similar low scores of knowledge across both groups as well as a greater number of erroneous beliefs among law enforcement officers. Second, we compared knowledge and erroneous beliefs of officers who had undergone training in investigative interviewing (n = 41) with those of their untrained counterparts (n = 159). Similar low scores in knowledge and false beliefs were found. However, when comparing officers who reported conducting five or more interviews per month (n = 82) to officers who reported conducting zero interviews per month (n = 43), we found that the first group expressed more erroneous beliefs. The results are discussed in line with previous research, in particular, studies on investigative interview practices.